The Hawthorne Effect in Eye-blinking: Awareness that One's Blinks are Being Counted Alters Blink Behavior. (1st November 2020) - Shaafi Kabiri, Nina; Brooks, Chris; Comery, Tom; Kelley, Michael Erb; Fried, Pete; Bhangu, Jaspreet; Thomas, Kevin
ABSTRACT: Purpose : Spontaneous eye-blink rate is the number of involuntary blinks performed during a certain period of time. Assessing blink rate in humans provides valuable physiological and behavioral data for studying neuropathology and emotional states. Cognitive states, including awareness on the part of the subject that his or her blinks are being counted, may influence blink activity and confound blink rate measurements. The goal of this study was to provide direct experimental evaluation of the hypothesis that subject awareness affects tasked-based blink activity. Materials and methods : 30 young healthy adult males with normal vision underwent a series of tasks – viewing images, talking, sitting quietly, and cross fixation – while being video recorded. Each subject completed the tasks naively, then repeated them after being explicitly told their blink rate was being measured. Blink rate was measured through minute-by-minute blink counts by human raters. Results : We found a transitory impact on blink count during the first and third minute of a passive image-viewing task that occurred immediately after subjects were informed of their eye blinks being counted. However, the overall blink rate across the 7-min passive image-viewing task was not influenced. In three other tasks – fixation, silence, and conversation – we observed no statistically significant difference in minute-by-minute blink count or overall blink rate. Conclusions : We conclude that informing a subject that his eye blinks are being counted exerts a modest but significant acute influence on blinking activity, but critically does not appear to confound blink rate over prolonged tasks.